Factors Affecting Trust Among Natural Resources Stakeholders, Partners, and Strategic Alliance Members: A Meta-Analytic Investigation - Ford, J. Kevin; Riley, Shawn J.; Lauricella, Taylor K.; Van Fossen, Jenna A. (Frontiers in Communication, 2020)
Trust, defined as a willingness of one entity (e.g., stakeholders) to be vulnerable to the discretionary actions of another (e.g., a wildlife management agencies), is a key attribute of effective environmental management. A lack of clarity about which factors matter most in developing and sustaining trust creates an impediment to good governance. Our objective was to derive a set of antecedents of trust from research reported in peer-reviewed literature in natural resource and environmental science, management and policy domains. We conducted a meta-analysis of the relationships between trust and seven antecedents: reputation, communication, shared norms and values, cooperation/support, negative past behaviors, satisfaction with/quality of services, and fairness. We also examined whether relationships between antecedents and trust differ depending on whether the target of trust is a specific person or the organization as an entity, as well as whether the relationship with the referent of trust is horizontal (i.e., between natural resource agencies partnering together) or vertical (i.e., between stakeholders and agencies). Results provide estimates of relationships between each antecedent and trust, as well as the relative importance of the antecedents in predicting trust. We conclude by evaluating the state of the literature on trust and providing recommendations for future research.